Main challenges for the Greek national security against the geopolitical changes in the Balkans during the period 1918–1923 - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2020)
The aim of the article is to show the role of the Balkan states within the Greek foreign policy during the period 1918–1923, on the base of diplomatic correspondence and historiography. The consequences of the military conflict with Turkey (1918–1922) and the internal problems, constantly harassing the socio-political life of Greece, seriously weakened its ability to impact effectively on particular geopolitical problems in the Balkan region. The Greek regional policy could be achieved, completely or partially, only with close cooperation with the powers from outside. It was connected with such cases as the delimitation of the Albanian frontier or the solution of the Western Thrace question in 1920. On the other hand, the proceedings of the Greek diplomats were determined by the belief that due to the unresolved territorial and national controversies, especially in the issue of the Macedonian and Thracian lands, the particular Balkan states were dependent on each other on the international arena. That is why the Greek diplomacy started apply the tactics of balance of power in the region, aiming at the creation of less or more stable bilateral political constructions with the Kingdom SCS (Yugoslavia) and Romania. Their aim was to ensure the advantage over the competitors on the Balkan arena, especially over Bulgarian and Turkish revisionist agendas.